(untitled) (Journal of Informatics Education and Research, 2026)
This research paper explores how sensory branding affects customer loyalty in Gujarat’s hotel industry. The study aims to provide valuable insights into the connection between sensory experiences and customer loyalty. The study also established a theoretical foundation through a comprehensive literature review where the study connects key concepts in sensory branding and customer loyalty. The methodology section outlines the thorough process utilized for data collection and analysis which ensures the reliability of the findings. The paper takes a comprehensive approach, incorporating aspects of marketing, psychology, and consumer behavior to build a well-rounded perspective. In conclusion, this study aims to improve the discourse on sensory branding’s impact within the unique context of the Gujarat hotel industry which promotes by guiding industry practices for optimal brand management. Objective: Investigating the impact of sensory branding on customer loyalty in Gujarat’s hotel industry. Findings and Implications: The study revealed positive associations between sensory branding components and customer loyalty in Gujarat’s hotel industry. These findings suggest that strategically enhancing sensory experiences can contribute to improved customer loyalty, providing practical insights for marketers and hotel managers in optimizing their branding strategies. Originality/Value: This research contributes novel insights to the discourse on sensory branding within the unique context of Gujarat, offering valuable perspectives for optimizing brand management practices in the hotel industry.